MicroRNA-125b protects liver from ischemia/reperfusion injury via inhibiting TRAF6 and NF-κB pathway. Issue 5 (4th May 2019) - Huang, Zuotian; Zheng, Daofeng; Pu, Junliang; Dai, Jiangwen; Zhang, Yuchi; Zhang, Wanqiu; Wu, Zhongjun
ABSTRACT: MicroRNA-125b (miR-125b), which was previously proved to be a potential immunomodulator in various disease, attenuated mouse hepatic ischemia/reperfusion (I/R) injury in this study. miR-125b was decreased in RAW 264.7 cells exposed to hypoxia/reoxygenation (H/R). The expression of IL-1β, IL-6 and TNF-α in both serum and supernate were reduced in miR-125b over-expression groups. The hepatic histopathological changes were reduced in miR-125b agomir groups. In the miR-125b antagomir groups, serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were significantly elevated compared with negative control (NC) groups. The protein expression of TNF receptor-associated factor 6 (TRAF6), IL-1β and the phosphorylation of p65 (p-p65) were suppressed by the up-regulation of miR-125b. Furthermore, the nuclear translocation of p-p65, measured by immunofluorescence, was enhanced by the miR-125b inhibitors. In conclusion, our study indicates that miR-125b protects liver from hepatic I/R injury via inhibiting TRAF6 and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signal pathway. Graphical abstract: : miR-125b attenuates hepatic I/R injury by suppressing TRAF6/NF-κB.